Saturday

April 19, 2014

April 19, 2014

Posted by **j.** on Thursday, January 27, 2011 at 9:08am.

- trig -
**drwls**, Thursday, January 27, 2011 at 10:24amCombine similar terms. For example, the two "x^2" terms combine to give

3x^2 -5x^2 = -2x^2

You can also combine the two 'x' terms, to get one 'x' term and the two constants also.

Don't forget that the "-" in front of

(5x^2+7x-7) changes the sign of every term inside the parentheses, before you combine similar terms.

You should end up with

-2x^2 -12x +11

**Related Questions**

Math - Can someone please check my answers below for accurateness? The ...

Math - Simplify. (5x2 + 3x - 7) - (x2 - 7x + 4) Simplify. (5x^2 + 3x - 7) - (x^2...

maths - solve the following simultaneous equation: 5x+2y=29 x-y=-4 2x-y=-1 3x-y=...

math, beginning algebra - how do i solve the following equations. Problem # 1 3x...

Math - I can not figure out the next step can someone help (x+3)*4+(x-3)*3=-5x ...

Intermediate Algebra - Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^...

Troy - Can someone check my answers for the following problems. Simplify. Assume...

algebra - 7x-8y=1 5x+37=y sub the second equation into the first: 7x - 8(5x+37...

Algebra II - Assume that no denomenator equals 0. (7x^2+3x-9)-(-x^2+8x-3) = 7x^2...

Algebra - simplify: [(2x^2+5x-6)/(5x^2+7x-6)]*[(20x^2-7x-3)/(6x^2-25x+4)]/[(4x^2...